PEMELIHARAAN IKAN GURAMI (Osphoronemus gouramy Lac.) DALAM WADAH AKUARIUM DIBERI PAKAN CACING SUTRA (Tubifex sp) PADA STRATA VERTIKAL - Syahrizal Syahrizal; Z Rustam; S Hajar (Universitas Batanghari Jambi, 2015)
This experiment aims to look at the effect of feeding silk worms (Tubifex sp) on the vertical strata in the aquarium container in the maintenance of carp (Osphoronemus gourami). This research was carried out for 30 days with a completely randomized design with 4 treatments and 3 repetitions. Treatment A (top feeding zone), B (middle feeding zone 1), C (middle feeding zone 2), and treatment D (zone bottom-feeding).After analyzed by ANOVA and LSD (Significant Difference) research shows that the average biomass growth body length and weight of the fish is best in treatment C respectively by 6.82 cm and 3.30 grams of the water level 10 cm zone of basic aquarium (P <0.5). While the average percentage of the best survival was also contained in C treatment that is equal to 98%.Keywords: natural feed, hatchery fish and freshwater fish